Life Course Tobacco Smoking and Risk of HPV-Negative Squamous Cell Carcinomas of Oral Cavity in Two Countries - Madathil, Sreenath; Rousseau, Marie-Claude; Durán, Doris; Alli, Babatunde Y.; Joseph, Lawrence; Nicolau, Belinda (Frontiers in Oral Health, 2022)
Background: Tobacco smoking remains one of the major risk factors for oral cancers (OCC), a subgroup of head and neck cancer less attributed to human papillomavirus (HPV) infection. Although a strong dose-dependent association between tobacco smoking and OCC exists, several important questions on age-dependent effects of this habit remain unanswered. We investigated which life course hypothesis best describes the association between tobacco smoking and HPV-negative (HPV-ve) OCC in Canada and India. Method: We used data from the HeNCe Life study, a hospital-based case‐control study conducted in Canada and India, using similar protocols. Cases were newly diagnosed subjects with primary squamous cell carcinomas of the head and neck region. Control subjects were non‐cancer patients selected from various outpatient clinics in a hospital located in the same catchment area as the cases and frequency‐matched to cases according to age and sex. We collected information on an array of life course exposures using a structured questionnaire with the help of a life grid. Tobacco exposure (pack-years) during three life periods (≤ 30 years, 31- 50 years and > 50 years of age) was calculated from the entire life course history of smoking. We used CDx brushes to collect oral exfoliated cells. Alpha HPV DNA detection and genotyping were performed for 36 HPV genotypes using the linear array. Participants who tested positive HPV were excluded from the analysis. We used the Bayesian relevant life course exposure model (BRLM) to identify the life course hypothesis that best described the relationship between tobacco smoking and HPV-ve OCC. Results: We show evidence for a late-life sensitive period (> 50 years of age) for tobacco smoking in relation to the risk of HPV-ve OCC in both Canada and India. An increase of one pack-year of tobacco smoking increased the risk of OCC by approximately 3% in both countries. Conclusion: Our findings from Canadian and Indian data suggest that smoking tobacco after 50 years of age may carry a higher risk of developing oral cancer than earlier in life. Further studies are warranted to confirm the results.